Chinese herbal formula Fuzheng Huayu alleviates CCl4-induced liver fibrosis in rats: a transcriptomic and proteomic analysis - DONG Shu; CAI Fei-fei; CHEN Qi-long; SONG Ya-nan; SUN Yang; WEI Bin; LI Xiao-yan; HU Yi-yang; LIU Ping; SU Shi-bing (Acta Pharmacologica Sinica, 2018)
Abstract Liver fibrosis is a consequence of chronic liver disease that can progress to liver cirrhosis or even hepatocarcinoma. Fuzheng Huayu (FZHY), a Chinese herbal formula, has been shown to exert anti-fibrotic effects. To better understand the molecular mechanisms underlying the anti-fibrotic effects of FZHY, we analyzed transcriptomic and proteomic combination profiles in CCl4-induced liver fibrosis in rats, which were treated with extracted FZHY powder (0.35 g·kg–1·d–1, ig) for 3 weeks. We showed that FZHY administration significantly improved liver function, alleviated hepatic inflammatory and fibrotic changes, and decreased the hydroxyproline content in the livers of CCl4-treated rats. When their liver tissues were examined using microarray and iTRAQ, we found 255 differentially expressed genes (fold change ≥1.5, P